25 Centuries of lead white manufacturing processes identified by 13C and 14C carbon isotopes. (December 2022) - Messager, C.; Beck, L.; Blamart, D.; Richard, P.; Germain, T.; Batur, K.; Gonzalez, V.; Foy, E.
Graphical abstract: Highlights: Lead carbonate production processes are determined by carbon isotope analysis. Coupling 13 C and 14 C gives important clues to lead white pigment synthesis. 14 C distinguishes ancient and modern lead whites and dates historical productions. δ 13 C identifies the carbon source involved in lead white production. C isotopes analysis confirms lead white recipes of the historical literature. Abstract: Synthetic lead carbonates, cerussite and hydrocerussite, have been used for artistic and cosmetic purposes since Antiquity. Commonly known as lead white, the recipes for the manufacture of this pigment are recounted in many treatises on painting. Depending on the period considered, these two lead carbonates are derived either from a corrosion process or from industrial methods. In both cases, a carbon input, mainly CO2, is necessary to complete the synthesis of this pigment. Its origin depends on the historical period: initially, CO2 came only from microbial activity or the fermentation of organic matter, and from the 19th century on, it was derived mainly from fossil materials. Thus, lead white mainly acquires a 14 C and 13 C isotopic signature that reflects, to the nearest isotopic fractionation, the nature of the reactants used in its synthesis. In this article, we study the carbon isotopic signature of synthetic lead carbonates by Accelerator Mass Spectrometry (AMS) and Isotopic Ratio Mass Spectrometry (IRMS) through a large corpus of lead whites, composed of reference materials (known manufacturing processes) and of archaeological or museum collection pigments (unknown synthesis). Results show that the 14 C content discriminates the manufacturing processes of lead white according to the organic or fossil origin of the CO2 source, and provides absolute dates when pigments are produced by the corrosion of metallic lead in a natural fermentation medium. In addition, δ 13 C values identify the CO2 source more precisely. This study based on the combination of 14 C and 13 C data from lead carbonates provides information about the ingredients involved in the synthesis of lead white pigment and demonstrates a good correspondence between the carbon isotopic signature of lead carbonates and the descriptions of lead white recipes in the historical literature.